New AMS dates from the Sub-Neolithic sites in the Southern Buh area (Ukraine) and problems in the Buh-Dnister Culture chronology - Dmytro Haskevych; Eiko Endo; Dai Kunikita; Olexandr Yanevich (Documenta Praehistorica, 2019)
Ideas about the origin of the Buh-Dnister Culture under the influence of the Danube Early Neolithic were questioned by series of radiocarbon dates falling into the second half of the 7th millennium BC measured on bones at the Kyiv laboratory in 1998–2004. To start addressing this problem, 11 AMS dates on organic inclusions in the ceramic paste and charred residues on the surface of vessels were obtained at the Tokyo University laboratory. Apart from two heavily overestimated values, measured on samples with very low carbon content, they fall into the range of the 60th–46th century BC that correspond better to the primary views of this chronology. However, the issues of the time and direction of spreading of the first pottery in the region need further research.